2015
DOI: 10.1093/icvts/ivu447
|View full text |Cite
|
Sign up to set email alerts
|

How safe is it to train residents to perform off-pump coronary artery bypass surgery?: Table 1:

Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was, in [patients undergoing off-pump CABG] are [postoperative mortality and morbidity outcomes] acceptable when performed by [trainees]? Altogether more than 597 papers were found using the reported search, of which 8 represented the best evidence to answer the clinical question. Six retrospective cohort studies directly compared the performance of trainees and experienced surgeons in off-pump coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…8 Other small studies have shown comparable outcomes between consultant and resident surgeons with appropriate case selection. 9,10 This single-center retrospective study aimed to compare outcomes of OPCAB surgery in consultant and trainee cases.…”
Section: Introductionmentioning
confidence: 99%
“…8 Other small studies have shown comparable outcomes between consultant and resident surgeons with appropriate case selection. 9,10 This single-center retrospective study aimed to compare outcomes of OPCAB surgery in consultant and trainee cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, most currently available sources support the standpoint that the training does not increase the risk of the procedure. 3,14,15,17,19 Within our sample, the 30-day mortality and the incidence of postoperative complications were not significantly influenced by the number of already operated cases. Some trends can be seen (►Table 4), but there is no statistical significance despite the high sample volume.…”
Section: Commentmentioning
confidence: 58%
“…advantages, the adoption of this technically demanding procedure remains limited, with only a handful of cardiac surgeons venturing into this style of operation, likely owing to its significant learning curve (4). Our department has routinely performed OPCAB for patients with coronary artery diseases since 2011 and recently shifted to performing anaortic OPCAB with more frequency in cases that appear theoretically and anatomically reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…This strategic approach notably reduces the perioperative risk of stroke ( 3 ), yet it demands advanced techniques such as harvesting skeletonized arterial grafts to ensure sufficient length, the creation of composite grafts, and precise graft alignment during sequential bypass. Despite its patient-centric advantages, the adoption of this technically demanding procedure remains limited, with only a handful of cardiac surgeons venturing into this style of operation, likely owing to its significant learning curve ( 4 ). Our department has routinely performed OPCAB for patients with coronary artery diseases since 2011 and recently shifted to performing anaortic OPCAB with more frequency in cases that appear theoretically and anatomically reasonable.…”
Section: Introductionmentioning
confidence: 99%